Dephosphorylation of autoantigenic ribosomal P proteins during Fas-L induced apoptosis: a possible trigger for the development of the autoimmune response in patients with systemic lupus erythematosus. Issue 1 (1st January 2001) - Zampieri, S; Degen, W; Ghiradello, A; Doria, A; van Venrooij, W J
Abstract : OBJECTIVES: Autoimmune diseases are characterised by the production of autoantibodies against various autoantigens. In the past few years data have been published on a possible role of apoptosis in the development of autoimmunity. These include the finding that several autoantigens become modified (for example, by cleavage) during apoptosis, and the observation that these modified antigens are translocated to the cell surface. When the normal clearance of apoptotic cells somehow is disturbed, such modified antigens might become exposed to the immune system. Because acidic ribosomal P (phospho-) proteins targeted by autoantibodies in systemic lupus erythematosus (SLE) are also concentrated at the surface of apoptotic cells, this study aimed at investigating what modifications occur on these antigens during apoptosis. METHODS: Apoptosis in Jurkat cells was induced by Fas ligand (Fas-L), and the fate of autoantigenic P proteins was analysed in both normal and apoptotic total cell extracts. RESULTS: The autoantigenic P proteins were not cleaved but dephosphorylated during Fas-L induced apoptosis. This dephosphorylation was prevented when caspase activity was inhibited. CONCLUSIONS: As has been shown for other autoantigens targeted by autoantibodies in SLE, P proteins also are modified during apoptosis. P1 and P2 are completely dephosphorylated while P0 is partly dephosphorylated. Because the epitope targeted by autoantibodies normally is phosphorylated, it is possible that the apoptotic dephosphorylation of the antigen might be the trigger for the development of the autoimmune response against P proteins.